Classification of Multiple DNA Dyes Based on Inhibition Effects on Real-Time Loop-Mediated Isothermal Amplification (LAMP): Prospect for Point of Care Setting - Quyen, Than Linh; Ngo, Tien Anh; Bang, Dang Duong; Madsen, Mogens; Wolff, Anders (Frontiers in Microbiology, 2019)
LAMP has received great interest and it is widely utilized in life sciences for nucleic acid analysis. To monitor a real-time LAMP assay, fluorescence DNA dye is an indispensable component and therefore the selection of a suitable dye for real-time LAMP is a need. For the selection, we investigated the inhibition effects of twenty-three DNA dyes on real-time LAMP. Threshold time (Tt) value of each real-time LAMP was determined and used as an indicator of the inhibition effect. Based on the inhibition effects, the dyes were classified into four groups: 1) non-inhibition effect, 2) medium inhibition effect, 3) high inhibition effect, and 4) total inhibition. The signal to noise ratio (SNR) and the limit of detection (LOD) of the dyes in groups 1, 2 and 3 were further investigated, and possible inhibition mechanism of the DNA dyes on the real-time LAMP was suggested and discussed. Of the 23 dyes tested, SYTO 9, SYTO 82, SYTO 16, SYTO 13, and Miami Yellow are the best dyes with no inhibitory effect, low LOD and high SNR in the real-time LAMP reactions. The classification of the dyes will simplify the selection of fluorescence dye for real-time LAMP assays in point of care setting.